In Silico Study on Molecular Sequences for Identification of Paphiopedilum Species. (29th May 2018) - Vu, Huyen-Trang; Huynh, Phuong; Tran, Hoang-Dung; Le, Ly
Our study searched all available sequences of Paphiopedilum from NCBI (National Center for Biotechnology Information) and tested for their species resolution capability in single as well as in combination forms. A total of 28 loci were applied for analyses in the study. From the nuclear genome, the highest resolution was of LFY, followed by ACO, DEF 4, and RAD 51. These 4 loci were found to be even better than the popular region ITS for Paphiopedilum identification. Among the chloroplast regions, the intergenic spacer atpB - rbc L gave the highest species resolution (76.7%), followed by mat K, trn L, rpo C2, and ycf 1. The divergence of CHS, XDH, 18S, Nad 1, ccs A, rbc L, and ycf 2 was very low and should not be used as identifying markers for Paphiopedilum . In addition, 2-locus combinations could improve significantly the resolving capability for the genus, in which 14/36 data sets could be resolved completely (100%) with interspecies relationships. The indel information was also effective supporting data for molecular discrimination of species.